The great reversal : how America gave up on free markets - Philippon, Thomas (The Belknap Press of Harvard University Press, 2019)
"Why are cell-phone plans so much more expensive in the United States than in Europe? It seems a simple question, but the search for an answer took one of the world's leading economists on an unexpected journey through some of the most hotly debated issues in his field. He reached a surprising conclusion: American markets, once a model for the world, are giving up on healthy competition. In the age of Silicon Valley start-ups and millennial millionaires, he hardly expected this. But the data from his cutting-edge research proved undeniable. In this compelling tale of economic detective work, we follow Thomas Philippon as he works out the facts and consequences of industry concentration, shows how lobbying and campaign contributions have defanged antitrust regulators, and considers what all this means. Philippon argues that many key problems of the American economy are due not to the flaws of capitalism or globalization but to the concentration of corporate power. By lobbying against competition, the biggest firms drive profits higher while depressing wages and limiting opportunities for investment, innovation, and growth. For the sake of ordinary Americans, he concludes, government needs to get back to what it once did best: keeping the playing field level for competition. It's time to make American markets great--and free--again."--